Relationship Between Cognitive Fusion, Experiential Avoidance, and Obsessive–Compulsive Symptoms in Patients With Obsessive–Compulsive Disorder - Xiong, Ai; Lai, Xiong; Wu, Siliang; Yuan, Xin; Tang, Jun; Chen, Jinyuan; Liu, Yang; Hu, Maorong (Frontiers in Psychology, 2021)
Objective: This study aimed to explore the relationship among cognitive fusion, experiential avoidance, and obsessive–compulsive symptoms in patients with obsessive–compulsive disorder (OCD). Methods: A total of 118 outpatient and inpatient patients with OCD and 109 healthy participants gender and age matched were selected using cognitive fusion questionnaire (CFQ), acceptance and action questionnaire-2nd edition (AAQ-II), Yale–Brown scale for obsessive–compulsive symptoms, Hamilton anxiety scale, and Hamilton depression scale for questionnaire testing and data analysis. Results: The levels of cognitive fusion and experiential avoidance in the OCD group were significantly higher than those in the healthy control group (P<0.05). Regression analysis results showed that in predicting the total score of obsessive–compulsive symptoms, AAQ-Ⅱ (β = 0.233, P < 0.05) and CFQ (β = 0.262, P < 0.01) entered the equation, which explained 17.1% variance. In predicting anxiety, only AAQ-Ⅱ (β = 0.222, P < 0.05) entered the equation, which explained 13% variance. In the prediction of depression, the AAQ-Ⅱ (β = 0.412, P < 0.001) entered the equation, which explained 17.7% variance. Conclusion: Cognitive fusion and experiential avoidance may be important factors for the maintenance of OCD, and experiential avoidance can positively predict the anxiety and depression of OCD patients.